Neural sensitivity to trustworthiness cues from realistic face images is associated with temperament: An electrophysiological study with 6-month-old infants. (2nd November 2021) - Baccolo, Elisa; Quadrelli, Ermanno; Macchi Cassia, Viola
ABSTRACT: Discriminating facial cues to trustworthiness is a fundamental social skill whose developmental origins are still debated. Prior investigations used computer-generated faces, which might fail to reflect infants' face processing expertise. Here, Event-Related Potentials (ERPs) were recorded in Caucasian adults (N = 20, 7 males, M age = 25.25 years) and 6-month-old infants (N = 21, 10 males) in response to variations in trustworthiness intensity expressed by morphed images of realistic female faces associated with explicit trustworthiness judgments (Study 1). Preferential looking behavior in response to the same faces was also investigated in infants (N = 27, 11 males) (Study 2). ERP results showed that both age groups distinguished subtle stimulus differences, and that interindividual variability in neural sensitivity to these differences were associated with infants' temperament. No signs of stimulus differentiation emerged from infants' looking behavior. These findings contribute to the understanding of the developmental origins of human sensitivity to social cues from faces by extending prior evidence to more ecological stimuli and by unraveling the mediating role of temperament.